Bacterial infections in humans and nonhuman primates from Africa : expanding the knowledge - (:unkn) unknown (My University, 2021)
The close phylogenetic relationship between humans and other primates creates exceptionally high potential for pathogen exchange. The surveillance of pathogens in primates plays an important role in anticipating possible outbreaks. In this study, we conducted a molecular investigation of pathogenic bacteria in feces from African nonhuman primates (NHPs). We also investigated the pathogens shared by the human population and gorillas living in the same territory in the Republic of Congo. In total, 93% of NHPs (n=176) and 95% (n=38) of humans were found to carry at least one bacterium. Non-pallidum Treponema spp. (including T. succinifaciens, T. berlinense, and several potential new species) were recovered from stools of 70% of great apes, 88% of monkeys, and 79% of humans. Non-tuberculosis Mycobacterium spp. were also common in almost all NHP species as well as in humans. In addition, Acinetobacter spp., members of the primate gut microbiota, were mainly prevalent in human and gorilla. Pathogenic Leptospira spp. were highly present in humans (82%) and gorillas (66%) stool samples in Congo, but were absent in the other NHPs, therefore suggesting a possible gorillas-humans exchange. Particular attention will be necessary for enteropathogenic bacteria detected in humans such as Helicobacter pylori, Salmonella spp. (including S. typhi/paratyphi), Staphyloccocus aureus, and Tropheryma whipplei, some of which were also present in gorillas in the same territory (S. aureus and T. whipplei). This study enhances our knowledge of pathogenic bacteria that threaten African NHPs and humans by using a non-invasive sampling technique. Contact between humans and NHPs results in an exchange of pathogens. Ongoing surveillance, prevention, and treatment strategies alone will limit the spread of these infectious agents.
Keywords: African Research